Management of patients with multidrug-resistant organisms in rehabilitation facilities. Results of a survey in the Rhine-Main region, Germany, 2019 - Heudorf, Ursel; Berres, Marlene; Hofmann, Sabine; Steul, Katrin (German Medical Science GMS Publishing House, 2020)
Introduction: Multidrug-resistant organisms (MDRO) are a problem in medical facilities, including rehabilitation facilities in Germany. The national recommendations of the Commission for Hospital Hygiene and Infection Prevention (KRINKO) for prevention of and dealing with patients affected by MDRO are obligatory in rehabilitation facilities. A survey on the management of patients with MDRO in rehabilitation facilities in the Rhine-Main area is presented below.Materials and methods: The questions from a recently published survey in 45 rehabilitation facilities in 26 European countries (Doherty et al., 2019) were largely adopted unchanged: the type, size, and organization of the facility, availability of guidelines on MDRO, screening and (estimated) prevalence of MDRO, as well as special hygiene measures or restrictions for patients with MDRO.Results: 22 of the 43 institutions contacted participated (58%). All facilities had specific recommendations on how to deal with MDRO and more than 95% had adequate hygiene staff. The facilities encompassed 4,369 beds, with 3,909 (89%) of them in single-bed rooms, and only a few offered 3-bed rooms. About 20% of patients in general rehabilitation and 100% in early neurological rehabilitation are screened on admission. Six (27%) facilities refused to accept patients with MDRO. 40% of the facilities treated these patients in their own room and/or in a separate area. 27% of the facilities prohibited eating in the dining room and participating in hydrotherapy. Only 6 (27%) of the rehabilitation centers indicated that patients with MDRO are allowed to participate in full rehabilitation programs.Discussion: In accordance with the results of Doherty et al. (2019), there were many restrictions for rehabilitation patients with MDRO, indicating considerable need for improvement. Necessary hygiene recommendations to avoid the transmission of MDRO must not lead to rejection of inpatient rehabilitation or to less intensive rehabilitation.